Evaluation and Standardization of an Agglutination Test for Human Listeriosis - Larsen, Sandra A. (1972)
Human sera from patients with culturally confirmed listeriosis were tested for immunoglobulin M (IgM) and immunoglobulin G (IgG) agglutinating antibodies with trypsinized antigens of Listeria monocytogenes, Streptococcus faecalis, and Staphylococcus aureus. The response of humans to listeria infections is mainly IgM rather than IgG as found in animals. The antigens prepared from L. monocytogenes serotypes 1a, 1b, 2, 4b, and 4d were evaluated for specificity with normal sera, sera from patients with various other diseases, and sera from patients with listeriosis. The trypsinized antigens appeared to be specific for listeria antibodies with a cross-reaction rate of from 5.4 to 6%. Cross-reaction with S. aureus can be eliminated by absorption of the serum with S. aureus. This agglutination technique appears to be applicable for diagnostic testing, but, as with all serological procedures, both acute and convalescent sera should be tested.